2019
DOI: 10.1016/j.omtn.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Repeatability and Efficacy of Intradermal Electroporated Self-Replicating mRNA

Abstract: Local administration of naked self-replicating mRNA (sr-mRNA) in the skin or muscle using electroporation is effective but hampered by low repeatability. In this manuscript, we demonstrated that intradermal electroporation of sr-mRNA in combination with a protein-based RNase inhibitor increased the expression efficiency, success rate, and repeatability of the data. The RNase inhibitor should be added just before administration because storage of the inhibitor together with the sr-mRNA at −80°C resulted in a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…By evaluating the success rate as a function of the dose, we found that the percentage of successful injections gradually dropped when the dose of sa-RNA was lowered. We recently showed that this observation may be attributed to the presence of RNases and that the repeatability and efficacy of intradermal electroporated sa-RNA can be increased by adding a protein-based RNase inhibitor to the sa-RNA just before injection 42 . RNases are abundantly present on the skin, 43 and these RNases can contaminate the tip of the needle during injection.…”
Section: Discussionmentioning
confidence: 99%
“…By evaluating the success rate as a function of the dose, we found that the percentage of successful injections gradually dropped when the dose of sa-RNA was lowered. We recently showed that this observation may be attributed to the presence of RNases and that the repeatability and efficacy of intradermal electroporated sa-RNA can be increased by adding a protein-based RNase inhibitor to the sa-RNA just before injection 42 . RNases are abundantly present on the skin, 43 and these RNases can contaminate the tip of the needle during injection.…”
Section: Discussionmentioning
confidence: 99%
“… Plurifunctional CD4+ and CD8+ T cells [ 12 ] ta-SFV Nak. RNA ID HA Protection from influenza virus challenge [ 41 •• ] VEEV EP & LNP Luc Expression: EP, days 3−10; LNP, peak 24h [ 16 ] EP Pig High expression for 12 days [ 17 • ] Mouse Optimal expression in tail base versus flank [ 19 • ] EP+RNase inh. RNase inh.…”
Section: Vaccines Based On Naked Sarnamentioning
confidence: 99%
“… RNase inh. increased reproducibility [ 19 • ] LNP IM HIV ag.-lumaz. High HIV gp120-antibodies [ 37 ] SARS-2 spike SARS-2 neutralizing antibodies/cell response [ 45 •• ] LION Mouse/NHP SARS-2 neutralizing antibodies/cell response [ 46 •• ] LNPout HIV gp140 Mouse Equivalent antibody versus LNP with RNA inside [ 25 ] Exp Luc/GFP Hum skin exp Cephalin LNPs increased expression sevenfold [ 35 ] Cationic NLP IM Luc Mouse Enhanced complexation & delivery [ 34 ] NLC SEAP/ZIKV ag.…”
Section: Vaccines Based On Naked Sarnamentioning
confidence: 99%
See 2 more Smart Citations